Sustainable Marketing: The Influence Of Environmental Awareness On Consumer Purchasing Decisions - Suci Asfarani; Wenny Permata Sari; Irsandi, Irsandi (International Journal of Economics, Business and Innovation Research, 2024)
Environmental awareness has become an important factor influencing consumer behavior in recent decades. This study aims to analyze the influence of environmental awareness on consumer purchasing decisions towards sustainable products. Using a quantitative approach, data were collected through a survey of 200 respondents in Indonesia. The results showed that consumers with a high level of environmental awareness tend to choose environmentally friendly products. In addition, environmental education factors and brand trust in sustainable products were found to be key elements in decision making. This study provides valuable insights for companies to develop more effective sustainable marketing strategies to meet the needs of increasingly environmentally conscious consumers. Keywords : Sustainable Marketing, Environmental Awareness, Purchasing Decision, Sustainable Products